Clinical efficacy and safety of anticholinergic therapies in pediatric patients - Goldstein S (Dove Medical Press, 2019)
Stanley Goldstein Allergy and Asthma Care of Long Island, Rockville Centre, New York, NY, USA Abstract: The burden of uncontrolled asthma in children and adolescents is high. Treatment options for pediatric patients (aged under 18 years) with asthma are largely influenced by the Global Initiative for Asthma recommendations. Algorithms for adolescents (12–18 years) and adults are identical, but recommendations for children aged under 6 years and 6–11 years differ. Although the goals of treatment for pediatric patients with asthma are similar to those for adults, relatively few new therapies have been approved for this patient population within the last decade. Designing clinical trials involving children presents several challenges, notably that children are often less able to perform lung function tests, and traditional endpoints used in clinical trials with adults, such as forced expiratory volume in 1 second, asthma exacerbations and questionnaires, have limitations associated with their use in children. There are also ethical considerations related to the performance of longer placebo-controlled exacerbation trials. This review considers additional clinical endpoints to those traditionally reported, including forced expiratory flow at 25%–75% of forced vital capacity, which may help shed light on which treatments are most effective for use in pediatric patients with asthma. The pros and cons of specific and potentially clinically relevant endpoints are considered, along with device considerations and patient preferences that may enhance adherence and quality of life. Recent advances in the management of children and adolescents, including the US Food and Drug Administration and European Medicines Agency approval of tiotropium in patients with asthma aged 6 years and over, are also discussed. Keywords: asthma, anticholinergic, tiotropium, pediatric, children, adolescents